Gracillin Shows Potential Efficacy Against Non-Small Cell Lung Cancer Through Inhibiting the mTOR Pathway - Li, Yamei; Liu, Hai; Liu, Xiaoxuan; Xiao, Bang; Zhang, Minhong; Luo, Yaoling; Li, Mingchun; Yang, Jianqiong (Frontiers in Oncology, 2022)
Lung cancer remains one of the most common malignancies and is the leading cause of cancers-related deaths in the world. Non-small cell lung cancer (NSCLC) accounts for about 85% of lung cancers. Autophagy plays a very important role in the occurrence and development of tumors. Gracillin, a natural steroidal saponin, was isolated from Reineckia carnea which is commonly used to treat lung-related diseases. It was found that gracillin had great potential anti-tumor effects, but the mechanism remains unclear. To clarify the effect and mechanism of gracillin on NSCLC, human A549 cells and immunodeficient mice were used as models to investigate the anti-tumor effects of gracillin. Cell counting kit-8 (CCK-8) is used to detect cell proliferation. Transmission electron microscopy, PEGFP-LC3 plasmid, and western blot were used to detect the occurrence of autophagy and changes in autophagy signaling pathways. small interfering RNA (siRNA) and autophagy inhibitor were used to study the relationship between WIPI1 and autophagy. Finally, gracillin significantly inhibited the tumor growth and the proliferation of A549 cells. Autophagy factors WIPI1, Beclin-1, LC3-Ⅱ were significantly up-regulated, and P62 was significantly down-regulated. mTOR signaling pathway is inhibited. Autophagy was significantly reduced with WIPI1 silenced. So, WIPI1 was involved in gracillin-induced autophagy in A549 cells. Based on the above research, gracillin has strong antitumor activity against NSCLC, the anti-tumor mechanism may be inducing tumor cell autophagy, which eventually leads to cell death. We cautiously proposed that gracillin has great potential in the treatment of NSCLC.